2021
DOI: 10.1159/000515894
|View full text |Cite
|
Sign up to set email alerts
|

Association of p16 and Ki-67 with Risk of Recurrence in Previously Treated Cervical High-Grade Squamous Intraepithelial Lesions

Abstract: <b><i>Objective:</i></b> Our main objective was to assess the association between the markers p16 and Ki-67 and recurrence of disease in patients previously treated for cervical high-grade squamous intraepithelial lesion (HSIL). <b><i>Design:</i></b> This is a case-control study at the National Cancer Institute conducted between 2005 and 2015. Of the patients with a pathologically confirmed diagnosis of HSIL, 107 cases were selected. They were divided into 2 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…The role of p16 as a predictor of recurrent cervical disease is inconclusive, with limited and contradictory results. A large study in China reported a significant association between p16 and recurrent CIN2+ disease after conization and two-year follow-up (25). Compared with our study, the women were on average 10 years older and both their HIV and hrHPV status at baseline treatment were not disclosed, thus we cannot directly compare our findings.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The role of p16 as a predictor of recurrent cervical disease is inconclusive, with limited and contradictory results. A large study in China reported a significant association between p16 and recurrent CIN2+ disease after conization and two-year follow-up (25). Compared with our study, the women were on average 10 years older and both their HIV and hrHPV status at baseline treatment were not disclosed, thus we cannot directly compare our findings.…”
Section: Discussioncontrasting
confidence: 91%
“…In a smaller study of HIV-uninfected women with CIN2+, cervical disease recurrence was 37% at 18 months and the positive predictive value of p16 for recurrent CIN2+ disease was 42% ( 24 ). Similarly, in a study in Mexico, there was no association between the CIN2+ recurrence-free period and p16 expression ( p = 0.57) and few women were living with HIV (5%) ( 26 ). Moreover, p16 expression has been shown to be less sensitive than insulin-like growth factor II mRNA-binding protein (IMP3) expression at predicting progression and recurrence of HSIL among women living with HIV ( 28 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation